Acute-phase protein profile in horses subjected to different exercise protocols - Assuncao, Pedrita [UNESP]; Barbosa, Tatiana [UNESP]; Yonezawa, Leticia [UNESP]; Barbosa, Luciano [UNESP]; Watanabe, Marcus [UNESP]; Kohayagawa, Aguemi [UNESP]; Schmidt, Elizabeth [UNESP] (Canadian Vet Med Assoc, 2019)
High-intensity exercise can be associated with the occurrence of muscle injury, as well as the induction of an acute-phase response (APR). The present study aims to investigate the synthesis and profile of serum proteins in horses before and after participating in 2 different exercise protocols and to relate this profile to the presence or absence of muscular injury caused by exercise. Ten purebred Arabian (n = 5) and Criollo (n = 5) horses were subjected to 2 different tests on a treadmill, one consisting of short-duration and rapid-acceleration training (TRA) that was mostly anerobic and the other of long-duration and slow-acceleration training (TLD) that was predominantly aerobic. Blood samples were obtained before the beginning of exercise (T0) and at 6 post-exercise time points: immediately after (T1) and 30 min (T2), 3 h (T3), 12 h (T4), 24 h (T5), and 48 h (T6) after exercise. Hematocrit was determined by the microhematocrit method. Plasma and serum samples were prepared by centrifugation (1500 c g for 5 min) for plasma concentrations of fibrinogen, total serum proteins (TP), sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and creatine-kinase (CK) serum activity. Total protein concentration and CK serum activity were determined in an automated biochemistry analyzer. Fibrinogen was determined by the heat precipitation method in microhematocrit capillary tubes. Estimated concentrations of haptoglobin (Hp) significantly decreased after TRA and estimated concentrations of alpha-1 acid glycoprotein (AGP) significantly increased after both protocols at T2. Albumin increased after the TLD exercise protocol. Changes in hematocrit, haptoglobin, and albumin concentrations in horses subjected to different treadmill exercise protocols are related to a physiological response to hemoconcentration and hemolysis. Increases of AGP in the TLD protocol suggest the release of catecholamines as a response to avoid oxidative damage to tissue.